2020
DOI: 10.1002/ase.1949
|View full text |Cite
|
Sign up to set email alerts
|

Does spatial awareness training affect anatomy learning in medical students?

Abstract: Spatial ability (SA) is the cognitive capacity to understand and mentally manipulate concepts of objects, remembering relationships among their parts and those of their surroundings. Spatial ability provides a learning advantage in science and may be useful in anatomy and technical skills in health care. This study aimed to assess the relationship between SA and anatomy scores in first‐ and second‐year medical students. The training sessions focused on the analysis of the spatial component of objects' structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 105 publications
(151 reference statements)
0
24
1
6
Order By: Relevance
“…Does spatial awareness training affect anatomy learning in medical students? [12] In the perspective of the "kinesthetic learners," the answer is affirmative. Each approach has its own preparation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Does spatial awareness training affect anatomy learning in medical students? [12] In the perspective of the "kinesthetic learners," the answer is affirmative. Each approach has its own preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in support of kinesthetic learners, a recent of article answered the question "does spatial awareness training affect anatomy learning in medical students?" [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite that the ndings of this investigation are based on the cumulative scores of the semester, their skill ability constituted few scores as part of the practical reports. Therefore, they are not considered as basis for gender difference in this investigation, although a study assessed the spatial ability of medical students versus scores and observed gender variation [26].…”
Section: Discussionmentioning
confidence: 99%
“…Spatial awareness has been related to the capacity to manipulate 3D objects [70] and the literature is inconclusive when it comes to differences between males and females. Some authors believe there is no difference [71,72] while others support the idea that this ability is affected by gender [70] assigning better results to males than to females. The results of this study revealed statistical difference in only one of the highly rated items: extraction techniques, movements and force.…”
Section: Discussionmentioning
confidence: 99%